Professionalizing the Imam in Europe: Imam Training Programs as Sites of Deliberative Engagement - Boender, Welmoet ca. 20./21. Jh. (Religions, 2021)
This article discusses the first experiences of a supplementary imam training program that has been designed in the Netherlands for community-based imams, female religious leaders and mosque committee members. This “Professionalization of Imams in the Netherlands” program (PIN) was set up as a cooperation of the Representative Council of Muslims (CMO) and Vrije Universiteit Amsterdam, supported by state-subsidy. The article discusses how the initiators maneuvered within and beyond the politicized burden of expectation that has surrounded the establishment of European-based imam training programs for decades now. The article provides a unique insight into the program’s design, its collaborative partners and participants’ experiences, understanding the program as a site of deliberative engagement. It shows how the stakeholders ideally see ownership of the curriculum and trainee recruitment as a shared responsibility for the Muslim community and the public educational institution, whereas the state is willing to finance it. The article outlines how in this attempt the stakeholders must deal with some paradoxical dynamics that influence this notion of “shared ownership”. Sharing these analytical observations and recommendations will hopefully help stakeholders involved in setting up similar European programs to make rational decisions on content and format of (future) supplementary programs, within and beyond fields of power, authority and interest.